Construction of Meaning during a Pandemic: The Forgotten Role of Social Norms. Issue 14 (5th December 2020) - Rimal, Rajiv N.; Storey, J. Douglas
ABSTRACT: How social norms are formed likely has a bearing on the mechanisms underlying their effects on behavioral outcomes. We propose three mechanisms of norms formation – through direct experience, symbolically through media, or imaginatively – and introduce ideas about normative durability, normative subscription, normative volume, personal agency, and polarization of norms – that likely have a bearing on how norms affect behaviors. The COVID-19 pandemic has important implications for how norms are formed, which in turn invoke different underlying mechanisms in the relationship between social norms and behaviors. We propose a number of hypotheses for future studies to test.